THE EFFECT OF EMPLOYEE ENGAGEMENT AND JOB SATISFACTION ON EMPLOYEE LOYALTY IN THE CEMENT INDUSTRY - Bakti Setyadi; Dewi Sartika (SEAN Institute, 2023)
Employee loyalty is an important aspect for organizational success, affecting employee retention and overall performance. The purpose of the study was to explore the impact of employee engagement and job satisfaction on employee loyalty and identify the interaction between these factors using survey research method. Using convinance sampling technique, 98 employees from Semen Baturaja Palembang Limited Liability Company in all regions of Palembang were selected as the sample. Data was collected using a validated questionnaire instrument. The data will be analyzed using Smart PLS 3 software, with partial least squares (PLS) regression technique. The results show that Employee Engagement and Job satisfaction together have an influence of 67% on employee loyalty. Recommendations to companies in the manufacturing industry, especially the cement industry, who want to foster a loyal workforce are to focus on improving employee engagement and job satisfaction because it has the potential to have a positive impact on employee retention and overall organizational performance.